On the Detection of Neutral Loss, Islanding, and Meter Tampering in Electrical Installations - Syllas Frantzeskakis; Nick Rigogiannis; Christos Christodoulou; Nick Papanikolaou (IEEE Open Journal of the Industrial Electronics Society)
Neutral conductor loss on the upstream network of an electrical installation, as well as unintentional islanding operation, are two critical issues directly related to the safety of both human life and equipment of the electrical installation. Furthermore, another critical issue is meter tampering, which affects the operation and development of national power sectors. The state-of-the-art methods deal with those issues separately, without providing a holistic solution; moreover, they are facing several challenges in the prospect of mass storage installations at buildings. This article introduces a new scheme for the detection of neutral loss at the upstream network, the unintentional islanding conditions, and meter tampering simultaneously. In this context, a suitable technical solution is given by using one low-power H-bridge inverter and a current transformer, along with voltage and current measuring instruments. The detection scheme is based on the injection of a (zero-sequence) 12th harmonic voltage component in series with the utility voltage and the monitoring of the corresponding harmonic current component. The theoretical analysis of the proposed technique is discussed, whereas its effectiveness is validated through simulation and experimental results.